Formation of Quaternary Centers by Copper‐Catalyzed Asymmetric Conjugate Addition of Alkylzirconium Reagents1. Issue 31 (18th June 2013) - Sidera, Mireia; Roth, Philippe M. C.; Maksymowicz, Rebecca M.; Fletcher, Stephen P.
<x xml:space="preserve">Abstract</x> Pure and simple: Alkylzirconocenes generated in situ from simple alkenes are used in highly enantioselective copper‐catalyzed 1, 4‐addition reactions to trisubstituted cyclic enones to generate quaternary centers. These reactions operate at room temperature under a range of conditions and tolerate many functional groups. Cp=cyclopentadienyl, Tf=trifluoromethanesulfonyl.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>